Identification Of Bacteria In The Urine Of Women With Urinary Tract Infections (Uti) At Primaya Hospital Makassar - Petra Melenia Rahayu; Hartati Hartati; Sulfiani Sulfiani (CV. Inara, 2022)
Urinary Tract Infection (UTI) is caused by a group of gram-negative bacteria such as Escherichia coli, Proteus mirabilis, Klebsiella pneumonia, Citobacter, Enterobacter,Pseudomonasaeruginosa.In addition, gram-possitive bacteria can also cause UTI’s such as Staphylococcus epidermidis and Streptococcus faecalis UTI’s are more common in women because the urethra is shorter so contaminants can enter the urinary tract more easily. The type of research by using 10 urine samples on urine samples through urine culture examination.The type of urine used was urine while. This research aimed to determine what types of bacteria were found in the urine of women with Urinary Tract Infections (UTI) at Primaya Hospital Makassar. The results of the research from 10 urine samples of women with Urinary Tract Infections at Primaya Hospital Makassar, namely 3 samples found Escherichia coli bacteria, 6 samples were found Enterobacter agglomerans bacteria, and 1 samples was found Klebsiella sp. The most common type of bacteria was found in Enterobacter agglomerans.